Adenoid squamous cell carcinoma of upper lip, a rare variant of squamous cell carcinoma: A case report - Bhogavaram, Bharadwaj (J Family Med Prim Care, 2020)
Adenoid squamous cell carcinoma (ASCC) is a variant of squamous cell carcinoma. As this variant is rare it is difficult to distinguish it from other variants of squamous cell carcinoma. It commonly originates in the head and neck region as these parts are highly exposed to the sunlight. There are very few cases reported in the literature. Here we report a case in a 30-year-old male who reported with a nodular lesion over the upper lip with no unusual signs, which was confirmed as adenoid squamous cell carcinoma after various histopathological tests.